The Present Study Investigates The Impact of Guidance and Counseling Services on Student Learning Achievement in SMP 8 Sarolangu - Rahmah, Miftahul; Fadila, Fadila; Rizal, Syamsul (International Journal of Education, Information Technology, and Others, 2025)
Providing guidance and counseling services has become a critical response to students' increasingly complex challenges. These challenges, from academic pressure to social issues and mental health concerns, impede students' ability to thrive in their learning and personal lives. The efficacy of guidance and counseling services in addressing these challenges is well-documented, and their importance is growing in tandem with the complexity of the problems students face. The efficacy of guidance and counseling services in promoting positive student outcomes has been demonstrated by their ability to enhance learning skills, boost motivation, and mitigate problematic behaviors such as cheating, which can adversely impact academic performance. The study employed a quantitative approach, utilizing the Ex Post Facto method and a simple correlation design. The findings revealed a substantial impact of counseling services on student learning achievement. A contribution of 18.8% evidences the moderate relationship between counseling services and student learning achievement, while the remaining 81.2% is attributed to other variables not included in this study.